Lingue e culture in contatto - Caon, Fabio (Educazione Linguistica Language Education, 2016)
This article deals with the intercultural perspective in a communicative approach to language teaching. Other essays about intercultural communicative competence have been published in the previous issues of Educazione Linguistica. Language Education, and the editorial committee has chosen this topic as one of the cores for language teaching research these years, so  this essay is intended to provide the theoretical framework. This is the first issue entirely devoted to analysing the critical point of communication between speakers using a common language coming from different cultures - the German and the Italian cultures, in this case. Other monographic issues of EL.LE will follow, dealing with other pairs of cultures. A world intercultural map, which is being built on the basis of the model described in the essay, can be found in http://www.unive.it/labcom.